Pengaruh Live Streaming, Online Customer Review, Cashback Promotion dan Discount Flash Sale Terhadap Minat Beli Produk Shopee (Studi Kasus pada Pengguna Shopee di Kota Malang) - Soleha, Faridatus; Rizal, Mohammad; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The aim of this research is to find out and analyze the influence of Live Streaming, Online Customer Reviews, Cashback Promotions and Flash Sale Discounts on interest in buying Shopee products. Sampling was carried out among Shopee users in Malang City using the Maholtra formula so that a sample of 80 respondents was obtained. This research method uses multiple linear regression analysis with the SPSS 25 analysis tool. This research shows that the influence of Live Streaming, Online Customer Reviews, Cashback Promotion and Discount Flash Sale have a simultaneous effect on buying interest. Based on the t test (partial), Live Streaming and Cashback Promotion have a significant effect on buying interest, while Online Customer Reviews and Flash Sale Discounts do not have a significant effect on buying interest. Keywords: Live Streaming, Online Customer Review, Cashback Promotion, Flash Sale Discount, Purchase Interest